2019
DOI: 10.3389/fmicb.2019.00356
|View full text |Cite
|
Sign up to set email alerts
|

Saponin-Induced Shifts in the Rumen Microbiome and Metabolome of Young Cattle

Abstract: The aim of this study was to explore the effects of saponins on the rumen microbiota and the ruminal metabolome. Alfalfa hay (AH) and soybean hulls (SH) were used as fiber sources for the control diets. The AH and SH diets were supplemented with tea saponins resulting in two additional diets named AHS and SHS, respectively. These 4 diets were fed to 24 young male Holstein cattle ( n = 6 per diet). After 28 days of feeding, the rumen fluid from these cattle was collected using an oral sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 52 publications
7
77
1
Order By: Relevance
“…So far, the literature has shown that protozoa have different sensitivities to saponins due to the different compositions of sterols in their membranes . The antiprotozoal action of saponins is also limited by rumen microorganisms, which cause them to deglycosylate to sapogenins . It has been suggested that, for example, glycosidase‐inhibiting iminosugars could be used to reduce the effects of bacteria on saponins in the treatment .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, the literature has shown that protozoa have different sensitivities to saponins due to the different compositions of sterols in their membranes . The antiprotozoal action of saponins is also limited by rumen microorganisms, which cause them to deglycosylate to sapogenins . It has been suggested that, for example, glycosidase‐inhibiting iminosugars could be used to reduce the effects of bacteria on saponins in the treatment .…”
Section: Discussionmentioning
confidence: 99%
“…25 The antiprotozoal action of saponins is also limited by rumen microorganisms, which cause them to deglycosylate to sapogenins. 6 It has been suggested that, for example, glycosidase-inhibiting iminosugars could be used to reduce the effects of bacteria on saponins in the treatment. 25 To some extent, saponins also exhibit bacteriolytic activity in the rumen.…”
Section: Hohenheim Gas Test Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, plant-derived bioactive compounds have been concerned for its potential alternatives to growth promoting antibiotics in ruminant production [1][2]. Garlic (Allium sativum L.), which has been widely used as a foodstuff in the world, contains numerous active metabolites including sulfur compounds (allicin, alliin, diallyl sul de, and diallyl trisul de) [3][4].…”
Section: Introductionmentioning
confidence: 99%